Talking India - Nandy, Ashis; Jahanbegloo, Ramin (New Delhi ; Oxford : Oxford University Press, 2006)
Brings together a series of interviews conducted by noted Iranian social scientist, Ramin Jahanbagloo. These interviews cover the ideas of Indian-ness, Indian thought, religion politics, secularism, and pluralism, as well as Gandhi, India and Pakistan, democracy, globalization and culture.
Description based on print version record.
Keywords: Politics and culture -- India; India -- Intellectual life